Pullout behavior of lap splice connections between double-steel-plate composite walls and RC raft foundation in nuclear engineering. (1st March 2021) - Kong, Si-Yu; Fan, Jian-Sheng; Nie, Xin; Ding, Ran; Sun, Yun-Lun; Chen, Yan
Highlights: Eight 1/2 scaled DSC wall – RC foundation connections were tested with monotonic tensile loading. Influence of locations of lapped bars and tie configurations are investigated. Design recommendations on tie bars, lapped bars and shear studs are given. A new formula is proposed to design the tie bars considering the nonlinear strain distribution. A new tie form using internal steel webs is proposed as a promising alternative form of tie bars. Abstract: Considering the flexibility of construction and convenience of transportation, the lap splice connection using dowel or lapped bars between double-steel-plate composite (DSC) walls and reinforced concrete (RC) raft foundation is becoming increasingly popular in nuclear engineering. Because the anchorage of dowel or lapped bars in RC members has already been stipulated by many codes, this study mainly focus on the portion in DSC wall of this connection. Eight 1/2 scaled DSC wall – RC foundation connection specimens were tested with monotonic tensile loading to study the pullout mechanism of this connection and provide solid basis for design. The investigated variables are the locations of lapped bars and tie configuration including the spacing and diameter of tie bars. A new tie form using internal steel webs instead of tie bars is also proposed. The test results are analyzed and discussed in terms of crack pattern, load-displacement relations, strains of key components including steel faceplates, tie bars and lapped bars. Based on the experimental findings and previous research, five possible failure modes are concluded and the steel faceplates yielding is regarded as the design target. To avoid the other failure modes, design recommendations on tie bars, lapped bars and shear studs are given. Particularly, a new formula is proposed to design the tie bars to avoid splitting failure based on the nonlinear strain distribution along the length of connection. In addition, the internal steel webs are recommended as a promising alternative forms of tie bars, which has shown better mechanical performance as well as more convenient construction process.